Influence of Sm3+:Ag codoping on structural and spectroscopic properties of lead tellurite glass ceramics. Issue 2 (March 2015) - Bolundut, Liviu; Culea, Eugen; Borodi, Gheorghe; Stefan, Razvan; Munteanu, Constantin; Pascuta, Petru
Abstract: Lead tellurite glass ceramics doped with Sm2 O3 and codoped with fixed amounts of silver (Ag2 O or Ag metallic nanoparticles, AgNPs) have been studied by X-ray diffraction (XRD), density measurements, Fourier transform infrared (FTIR), diffuse reflectance ultraviolet–visible (DR-UV–vis) and photoluminescence (PL) spectroscopies. The crystallite size and the quantitative ratio of the crystallographic phases in the samples were evaluated from the XRD data. FTIR spectroscopy data show that the glass ceramics network mainly consists of TeO3 and TeO4 structural units and the conversion between these units depends on the Sm2 O3 content and the nature of the codopant (Ag2 O or AgNPs) present in the samples. The DR-UV–vis spectra of studied samples were recorded in the 350–1000 nm spectral range at room temperature. The optical band gap ( E g opt ) for the studied glass ceramics were calculated from the DR-UV–vis spectra. The important peaks evidenced by PL spectroscopy measurements are due to the Pb 2+ ions and Sm 3+ ions present in the studied samples. The Sm 3+ :Ag codoping was found to produce quenching of the luminescence emission of Sm 3+ ions in the studied samples.